Advances in neurotechnology, electronics and informatics : revised selected papers from the 2nd International Congress on Neurotechnology, Electronics and Informatics (NEUROTECHNIX 2014), October 25-26, Rome, Italy /: revised selected papers from the 2nd International Congress on Neurotechnology, Electronics and Informatics (NEUROTECHNIX 2014), October 25-26, Rome, Italy. ([2016]) - Unknown
No abstract available